IMPROVING THE STUDENTS’ SPEAKING ABILITY BY USING MIND MAPPING AND GUIDED QUESTIONS AT FOURTH SEMESTER OF ENGLISH EDUCATION STUDY PROGRAM AT ISLAMIC UNIVERSITY OF INDRAGIRI TEMBILAHAN - Mustajib, Agus (ENGLISH JOURNAL OF INDRAGIRI, 2017)
This objective of this research is to know whether Mind Mapping is more effective than Guided Question in teaching speaking for fourth semester of English education study Program at Islamic University of Indragiri Tembilahan. In experimental research, the researcher deals with the research instrument of collecting data: (1) giving the pre-test (2) dividing the classes who have Mind Mapping and Guided Question (3) applying the teaching technique to the students (4) giving post test, and (5) analyzing the students’ score to  decide the teaching technique whether or not it is effectives. The research findings show that the use of Mind Mapping can affect the students’ speaking ability optimally. It is proved from research findings which t-observed value 3.189 is higher than t-table of 1.671 at the significant level of 5% which means that the Mind Mapping is more effective than Guided Question to speaking ability; therefore it is recommended that the lecturers are suggested to apply Mind Mapping in speaking activity, to be more creative and innovative in using various kinds of interesting teaching technique with accompany the materials.